2005
DOI: 10.1532/ijh97.e0422
|View full text |Cite
|
Sign up to set email alerts
|

Familial Mediterranean Fever and E148Q Pyrin Gene Mutation in Greece

Abstract: Familial Mediterranean fever (FMF) is an inherited disease characterized by recurrent inflammatory polyserositis. Although FMF is classically expected only in Middle East populations, it is becoming evident that the disease affects more groups than initially thought. The disease is associated with a number of mutations of the MEFV gene, which codes for a protein named pyrin. The role of E148Q pyrin gene mutation in the development of FMF remains inconclusive. Some authors believe it causes the disease, whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 23 publications
0
10
0
1
Order By: Relevance
“…55,56 Several studies describe p.Glu148Gln as a disease-causing mutation. [57][58][59][60][61][62] The Infevers Web site also lists it as causing disease-related symptoms. Other studies have not found p.Glu148Gln to be associated with clinical disease and have, therefore, considered it a benign polymorphism.…”
Section: Genotype-phenotype Correlationsmentioning
confidence: 99%
“…55,56 Several studies describe p.Glu148Gln as a disease-causing mutation. [57][58][59][60][61][62] The Infevers Web site also lists it as causing disease-related symptoms. Other studies have not found p.Glu148Gln to be associated with clinical disease and have, therefore, considered it a benign polymorphism.…”
Section: Genotype-phenotype Correlationsmentioning
confidence: 99%
“…The p.E148Q (c.442G.C) variation situated in exon 2 was initially described as a mutation, 3 but its implication in FMF remains controversial. [4][5][6][7][8][9] By using a population-based approach, we recently showed that the p.E148Q allele is a benign polymorphism. 7 Here, we use pedigree analysis to assess the association of the p.E148Q allele with FMF.…”
mentioning
confidence: 99%
“…The E148Q allele appears to confer an inflammatory phenotype in Turkish individuals [12]. In a Greek population, the E148Q allele was found to be significantly more frequent in FMF patients than that in healthy controls [13]. Although FMF patients with E148Q allele have a heterozygous clinical presentation, some patients are symptomatic and colchicine treatment is required as demonstrated in our patient.…”
Section: Discussionmentioning
confidence: 50%